Determining the frequency of de novo germline mutations in DNA mismatch repair genes. Issue 8 (2nd June 2011) - Win, Aung Ko; Jenkins, Mark A; Buchanan, Daniel D; Clendenning, Mark; Young, Joanne P; Giles, Graham G; Goldblatt, Jack; Leggett, Barbara A; Hopper, John L; Thibodeau, Stephen N; Lindor, Noralane M
Abstract : Background: Carriers of a germline mutation in a DNA mismatch repair (MMR) gene—that is, persons with Lynch syndrome—have substantially high risks of colorectal (CRC), endometrial, and several other cancers. The proportion of carriers who have de novo mutations (not inherited from either parent) is not known. This study reports a case series of de novo mutations in MMR genes and estimates the frequency of de novo mutation in MMR genes using the Colon Cancer Family Registry. Methods: Screening for germline MLH1, MSH2, MSH6, and PMS2 mutations was performed for all incident CRC cases recruited from cancer registries (population based probands) displaying microsatellite instability (MSI) or loss of expression of MMR genes by immunohistochemistry (IHC) and probands with CRC in multi-case families recruited from clinics (clinic based probands), regardless of MSI or IHC status. All relatives of probands with a pathogenic mutation who donated a blood sample underwent testing for the mutation identified in the proband. Results: Of 261 probands (202 clinic based, 59 population based) with MMR gene mutations for whom it was possible to determine the origin of the mutation, six (2.3%, 95% CI 0.9% to 5.0%) were confirmed as de novo, and the remaining 255 (97.7%, 95% CI 95.0% to 99.1%) were inherited. Of the de novo mutation carriers, three were clinic based probands (1.5%, 95% CI 0.3% to 4.5%) and three were population based probands (5.1%, 95% CI 1.2% to 14.5%). Two were in MLH1, three in MSH2, and one in MSH6 . Conclusion: De novo MMR gene mutations are uncommon causes of Lynch syndrome.